Assemblage in visual art: exploring the techniques of arranging and attaching natural materials for primary schools / Kamal Baharom - Baharom, Kamal (2013)
Arts education is a very important curriculum in schools. Its existence is considered as a requirement by the experts in the form of creative thinking in students. Four basic areas of arts education curriculum that should be explored in the school are drawing, pattern making and design, developing and making buildings and recognizing traditional crafts. But the field of forming and making building are less practiced than in other fields especially in the assemblage artwork. In this study, the researcher proposes one of the ways, techniques or skills that is much easier for students to build assemblage artwork through arranging techniques and attaching natural materials compared to conventional techniques such as removing the material, molding and patches. Qualitative study based on teacher's observation finds the assemblage artwork in the forming and building activities is easier through these techniques to attract the students to apply rather than the conventional methods